Unveiling the Dual Struggle: Health Perils and Social Stigma among Minority Sanitary Workers - Zoraiz Tahir Chaudhry (Corresponding Author); Jawairia Mukhtar; Muhammad Abubakar; Kamran Khalid; Shahoodah Anwar (Al-Qanṭara, 2024)
This qualitative study investigates the intertwined challenges faced by minority sanitary workers in Pakistan, focusing on the Sargodha region. The research delves into the dual struggle encompassing occupational health hazards and social stigma experienced by these workers. Conducting in-depth interviews with 20 participants from diverse minority backgrounds and genders, this research uncovers multifaceted issues prevalent among these essential workers. Results of the study highlighted the precarious working conditions marked by the absence of adequate protective gear during waste disposal tasks, exposing them to toxic chemicals, infectious waste, and noxious fumes. Respiratory issues, including persistent coughing and chest discomfort, were prevalent due to prolonged exposure to pollutants. Additionally, injuries sustained during waste collection activities posed immediate health risks, compounded by the lack of proper safety measures. The study also uncovered the pervasive social stigma and discrimination faced by these workers, stemming from their occupation and minority status, leading to devaluation, societal exclusion, and marginalization. The findings underscore the urgent need for improved safety protocols, access to protective equipment, and enhanced working conditions to address occupational hazards. Furthermore, the study emphasizes the importance of social advocacy and policy interventions to mitigate societal stigmatization and discrimination against these essential yet vulnerable workers.